2020
DOI: 10.12703/r/9-30
|View full text |Cite
|
Sign up to set email alerts
|

Cutting-edge genetics in obsessive-compulsive disorder

Abstract: This article reviews recent advances in the genetics of obsessive-compulsive disorder (OCD). We cover work on the following: genome-wide association studies, whole-exome sequencing studies, copy number variation studies, gene expression, polygenic risk scores, gene–environment interaction, experimental animal systems, human cell models, imaging genetics, pharmacogenetics, and studies of endophenotypes. Findings from this work underscore the notion that the genetic architecture of OCD is highly complex and shar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 121 publications
(94 reference statements)
0
7
0
Order By: Relevance
“…Here we review genetic evidence obtained using approaches that employ both a diagnostic (case/control) and a dimensional (continuous phenotype) framework and discuss the implications for future genetic research of OCD. We only briefly address the genetic findings from studies using the diagnostic conceptual framework in OCD, as recent reviews have discussed these in depth [26][27][28][29]. The majority of this review focuses instead on recent advances in OCD genomics research by examining the evidence for genetic correlates of OCD using a dimensional perspective.…”
Section: Introductionmentioning
confidence: 99%
“…Here we review genetic evidence obtained using approaches that employ both a diagnostic (case/control) and a dimensional (continuous phenotype) framework and discuss the implications for future genetic research of OCD. We only briefly address the genetic findings from studies using the diagnostic conceptual framework in OCD, as recent reviews have discussed these in depth [26][27][28][29]. The majority of this review focuses instead on recent advances in OCD genomics research by examining the evidence for genetic correlates of OCD using a dimensional perspective.…”
Section: Introductionmentioning
confidence: 99%
“…Meta-analyses of GWAS have revealed that single nucleotide polymorphisms (SNPs) associated with increased risk for OCD significantly overlap with SNPs associated with increased putamen and nucleus accumbens (NAcc) volumes 83 and that genes associated with OCD and compulsivity significantly overlap with genes expressed in the ACC, NAcc, and amygdala. 84 These findings suggest that common genetic variants may underlie dysfunctions in several of the neurocircuits proposed in models of OCD (Table 1) (see also Saraiva et al 78 ). Yet, the functional impact and clinical translation of these genetic variants continue to be a challenge mainly due to the non-coding nature of the majority of these variants and their pleiotropic effects.…”
Section: Limitations Related To Etiological Factors Involved In Ocdmentioning
confidence: 87%
“…In terms of genetic factors, twin and family studies have shown that OCD is heritable, with elevated rates of OCD in firstdegree family members of OCD patients. [76][77][78] Twin studies indicate that this heritability largely reflects shared genetic rather than shared environmental factors. 76 Further, neuroimaging studies report shared neurocircuit dysfunctions in OCD patients and their unaffected siblings, including hyperactivity of the pre-supplementary motor area during response inhibition 79 and hyperactive error monitoring functions of the ACC, 80 which may reflect neuroendophenotypes of OCD, i.e., neurobiological markers of genetic risk for the disorder.…”
Section: Limitations Related To Etiological Factors Involved In Ocdmentioning
confidence: 99%
“…OCD is characterized by intrusive thoughts, images, or impulses, and/or repetitive compulsive behaviors (2). OCD is widely considered to be polygenic in origin (3)(4)(5), and family and twin studies have estimated heritability as high as 50% (6,7). Two genome-wide association studies (GWAS) of OCD have been published to date, as well as a meta-analysis (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%